Figures 109-112. An Electric Machine and Electrometers - Palmer, Edward (Palmer's New Catalogue, with Three Hundred Engravings of Apparatus, Illustrative of Chemistry, Pneumatics, Frictional and Voltaic Electricity, Electro Magnetism, Optics, &c., 1840)
Figure 109. Double 18-ich Electrical Machine a very splendid and powerful instrument, on Woodward's principle. Figure 110. Harris's Unit Jar Electrometer with graduated slider, for charging other Leyden jars, or batteries, with known proportions of electricity. Figure 111. Coulomb's Torsion Electrometer for measuring with great accuracy small quantities of electricity. Figure 112. Harris's Balance Beam Electrometer for estimating in gran weights the attractive power exerted between two oppositely electrified surfaces such as the outer and inner coatings of a Leyden jar or batter, &c. These illustrations are part of Palmer's New Catalogue by Edward Palmer (1803-1872), regarded as the earliest, freely-accessible sales catalog of commercially available chemicals and scientific apparatus. The catalog provides insight into the costs and considerations of equipping laboratories during the early Victorian period. Featuring 292 engraved figures, the catalog is digitized in its entirety.
Keywords: Scientific apparatus and instruments; Commercial catalogs; Electric machines; Magneto-electric machines; Electrometer; Science--Experiments; Scientific apparatus and instruments industry